2005
DOI: 10.1093/gerona/60.11.1432
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Accelerates Wound Healing Among Healthy Older Adults: A Preliminary Investigation

Abstract: Background. Older adults are likely to experience delayed rates of wound healing, impaired neuroendocrine responsiveness, and increased daily stress. Exercise activity has been shown to have a positive effect on physiological functioning and psychological functioning among older adults. This study evaluated the effect of a 3-month exercise program on wound healing, neuroendocrine function, and perceived stress among healthy older adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
90
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 21 publications
6
90
0
1
Order By: Relevance
“…Similar to the Emery study referenced above, 43 it was found that exercise significantly sped healing compared to healing rate in sedentary controls. Interestingly, the major differences in healing rate between groups occurred early (1-5 days) postwounding, indicating that exercise may be exerting its effects on healing during this phase of healing.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…Similar to the Emery study referenced above, 43 it was found that exercise significantly sped healing compared to healing rate in sedentary controls. Interestingly, the major differences in healing rate between groups occurred early (1-5 days) postwounding, indicating that exercise may be exerting its effects on healing during this phase of healing.…”
supporting
confidence: 72%
“…In a study of older adults published by Emery in 2005, 43 cutaneous wounds were applied one month after onset of the exercise intervention. Wound healing was then assessed until total closure of the wound.…”
mentioning
confidence: 99%
“…Data was requested from these authors [47-49]; however, two studies were excluded as the authors could not be contacted [49] or could not access the required data to allow calculation of an effect size r [48]. In addition, one [50] of the intervention studies [47,50] was excluded from the meta-analysis because it did not provide evidence concerning the strength of the relationship between stress and wound healing, as the intervention failed to change levels of stress. Therefore, 12 studies were included in the meta-analysis.…”
Section: Data Synthesis For Meta-analysis Of a Subset Of Included Stumentioning
confidence: 99%
“…A variety of stressors were measured, the most popular (10 studies) being brief naturalistic stressors (i.e., surgical procedures and academic examinations) followed by global stress appraisals [43,45,50,63,67]. Less common were acute time limited stressors [22, 48,59], chronic stressors [64,65], stressful event sequences (i.e., marital difficulties) [48,62], and distant stressors [60].…”
Section: J Walburn Et Al / Journal Of Psychosomatic Research XX (20mentioning
confidence: 99%
See 1 more Smart Citation